2019
DOI: 10.3171/2018.6.spine18362
|View full text |Cite
|
Sign up to set email alerts
|

Current treatment strategy for newly diagnosed chordoma of the mobile spine and sacrum: results of an international survey

Abstract: OBJECTIVEThe purpose of this study was to investigate the spectrum of current treatment protocols for managing newly diagnosed chordoma of the mobile spine and sacrum.METHODSA survey on the treatment of spinal chordoma was distributed electronically to members of the AOSpine Knowledge Forum Tumor, including neurosurgeons, orthopedic surgeons, and radiation oncologists from North America, South America, Eur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 28 publications
0
29
0
2
Order By: Relevance
“…37 A recent survey by the AOKFT revealed large variations across some of the world's most experienced cancer centers in the use of radiation modalities in the setting of newly diagnosed spinal chordomas. 38 For tumors with which en bloc resection is feasible with acceptable morbidity, some centers are giving neoadjuvant radiation as a standard of care, other centers are administering routine postoperative radiation regardless of the surgical margins, and some centers are not pursuing any radiation treatment when wide/marginal margins are obtained. On the other hand, when en bloc resection would result in significant morbidity, some centers rely more heavily on neoadjuvant and adjuvant therapies with variation in the surgical procedure.…”
Section: Strong Very Lowmentioning
confidence: 99%
“…37 A recent survey by the AOKFT revealed large variations across some of the world's most experienced cancer centers in the use of radiation modalities in the setting of newly diagnosed spinal chordomas. 38 For tumors with which en bloc resection is feasible with acceptable morbidity, some centers are giving neoadjuvant radiation as a standard of care, other centers are administering routine postoperative radiation regardless of the surgical margins, and some centers are not pursuing any radiation treatment when wide/marginal margins are obtained. On the other hand, when en bloc resection would result in significant morbidity, some centers rely more heavily on neoadjuvant and adjuvant therapies with variation in the surgical procedure.…”
Section: Strong Very Lowmentioning
confidence: 99%
“…As seen in (Table 3), the most frequent lesions undergoing TES were sarcoma, metastasis, chordoma, and plasmacytoma. The literature clearly shows that TES results in superior oncologic outcome in terms of progression-free and overall survival for the following entities: sarcoma, GCT, chordoma and ABC [18][19][20][21][22][23]. In a recent consensus statement by the Chordoma Global Consensus group, it was agreed that extralesional resection is the treatment of choice for localized chordoma whenever feasible [1].…”
Section: Discussionmentioning
confidence: 99%
“…With the spinal complex anatomic structure and high potential of recurrence, the management of recurrent spinal chordoma was extremely big challenge for surgeons [16]. As for RRSC, how to decrease the risk of recurrence and prolong the OS was a tough issue due to its locally aggressive behavior and its resistance to adjuvant therapies [17,18]. Notably, it is the rst time to take NOR and FSI into consideration of prognosis of patients with RRSC.…”
Section: Discussionmentioning
confidence: 99%
“…Subtype analysis was described in Table 4. Subtotal resection, subtotal resection + RT, total piecemeal resection, total piecemeal resection + RT, and En bloc resection were used in 15,12,16,18, and 4 cases, respectively. Statistical analysis revealed that treatment method could make a signi cant difference in RFS (P < 0.001) and OS (P = 0.006), and patients undertaken total piecemeal resection and en bloc resection had longer RFS and OS.…”
Section: Patients' Baseline Informationmentioning
confidence: 99%